PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI KENAKALAN SISWA DI SMP NEGERI 2 KUBU KABUPATEN ROKAN HILIR - Ropikotul Husna; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Guidance and counseling is a means of educational institutions whose role is to guide, direct, and provide advice to students in solving a problem or in finding their potential, so it is very important that guidance and counseling services exist in a school. This research was conducted to find out more about the role of guidance and counseling teachers in overcoming student delinquency at SMP Negeri 2 Kubu, Rokan Hilir Regency. This research was conducted to find out: 1) How is the role of guidance and counseling teachers in overcoming student delinquency in SMP Negeri 2 Kubu Rokan Hilir Regency? 2) the what are obstacles of guidance and counseling teachers in overcoming student delinquency at SMP Negeri 2 Kubu Rokan hilir regency This research uses descriptive qualitative research methods. The results of the research were obtained from interviews with sources and also using comparisons from previous research. Factors causing child delinquency are influenced by 3 factors, namely, 1) student family factors, 2) the community that is near students, and 3) student friend factors. The form of role in overcoming student delinquency can be seen from the way teachers look for student pontensi, and motivate students to follow the norms that apply at school, besides that the role of the teacher can also help students in recognizing morals. Meanwhile, the obstacles of guidance and counseling teachers in overcoming student delinquency can be seen in the form of student discomfort with the lessons delivered by teachers who are considered less interesting in terms of teaching. In other forms, the obstacles of counseling guidance teachers can also be felt from the lack of student attendance in the teaching and learning process and the lack of communication between students and teachers. Keywords: Guidance and Counseling, Overcoming Student, Teacher Role.